An Experiment of the Actual Vertical Resolution of the Sub-bottom Profiler in an Anechoic Tank - WANG, Fangqi; DONG, Lifeng; DING, Jisheng; ZHOU, Xinghua; TAO, Changfei; LIN, Xubo; LIANG, Guanhui (Archives of Acoustics, 2019)
Sub-bottom profiler (SBP) is an acoustic instrument commonly used to survey underwater shallow geological structure and embedded objects whose most important performance parameter is the actual vertical resolution. This paper presented a methodology to measure and evaluate the actual vertical resolution of SBP based on an experiment in an anechoic tank, which was divided into three components: building of artificial geological model, measurement of acoustic parameters, and determination of actual vertical resolution of the acoustic profiles. First, the wedge-shaped geological model, whose thickness could be accurately controlled, was designed and built in an anechoic tank to try to directly measure the vertical resolution of SBP. Then, the acoustic pulse width of SBP was measured to calculate the theoretical general vertical resolution and extreme vertical resolution. Finally, based on the acoustic profiles obtained in the experiment, the method which was used to evaluate the actual vertical resolution by measuring the duration of reflection event was put forward. Due to comparing measurement data of different parameter settings of the SBP, the study has revealed that the SBP had the lowest resolution in the 4 kHz-500 μs setting, which was 226.5 μs, or 36.2 cm, and the highest resolution in the 15 kHz-67 μs setting, which was 72.7 μs, or 11.6 cm. The vertical resolution decreased with the increase of the pulse width. The results also showed that the actual resolution was close to the theoretical general resolution and far from the extreme resolution.